2017
DOI: 10.1159/000475530
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Heterogeneity in Lymphomas: A Different Breed

Abstract: The facts that cancer represents tissues consisting of heterogeneous neoplastic, as well as reactive, cell populations and that cancers of the same histotype may show profound differences in clinical behavior have long been recognized. With the advent of new technologies and the demands of precision medicine, the investigation of tumor heterogeneity has gained much interest. An understanding of intertumoral heterogeneity in patients with the same disease entity is necessary to optimally guide personalized trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 107 publications
0
24
0
Order By: Relevance
“…The tumor microenvironment (TME) is constituted by heterogeneous cellular populations including tumor cells and the surrounding non-malignant cells, such as numerous and distinct immune cells and stromal cells. Beyond the heterogeneity of the tumor cells (see above COO), the diversity and plasticity of the microenvironment also contributes to the intra-tumor heterogeneity ( 7 , 33 , 34 ). Strong evidences show that diverse immune subsets and their interactions within the tumor microenvironment are critical to diverse aspects of tumor biology, treatment response, and prognosis ( 35 , 36 ).…”
Section: Applications Of Scrna-seq: Deciphering Functional Diversity mentioning
confidence: 99%
“…The tumor microenvironment (TME) is constituted by heterogeneous cellular populations including tumor cells and the surrounding non-malignant cells, such as numerous and distinct immune cells and stromal cells. Beyond the heterogeneity of the tumor cells (see above COO), the diversity and plasticity of the microenvironment also contributes to the intra-tumor heterogeneity ( 7 , 33 , 34 ). Strong evidences show that diverse immune subsets and their interactions within the tumor microenvironment are critical to diverse aspects of tumor biology, treatment response, and prognosis ( 35 , 36 ).…”
Section: Applications Of Scrna-seq: Deciphering Functional Diversity mentioning
confidence: 99%
“…Besides the generally accepted fact that tumor heterogeneity itself inevitably results in acquired drug-resistance, because it can be viewed as a reservoir of preexisting drug-resistant clones, single tumor cell plasticity can lead to adaptive transcriptional and post-transcriptional changes that can result in the derivation of the so-called "drug-tolerant persister" (DTP) cells ( Figure 1A) [53]. It has…”
Section: Drug-tolerant Persister Cellsmentioning
confidence: 99%
“…Besides the generally accepted fact that tumor heterogeneity itself inevitably results in acquired drug-resistance, because it can be viewed as a reservoir of preexisting drug-resistant clones, single tumor cell plasticity can lead to adaptive transcriptional and post-transcriptional changes that can result in the derivation of the so-called "drug-tolerant persister" (DTP) cells ( Figure 1A) [53]. It has been demonstrated that DTP cells exposed to anti-tumor drugs exploit adaptive mutability (a process similar to the increased mutation rate of bacteria exposed to antibiotics), which is achieved through the down-regulation of mismatch repair and homologous recombination genes with concomitant overexpression of error-prone polymerases [54].…”
Section: Drug-tolerant Persister Cellsmentioning
confidence: 99%
“…With the application of high-dose methotrexate-based combination chemotherapy, the median overall survival rate of PCNSL increased from 12.5 months in the 1970s to 26 months in the 2010s (3). Similar to systemic DLBCL, approximately 50% of PCNSL patients relapse after treatment (4), and 10% to 15% of patients are primarily refractory (5). In cases of refractory or relapsed disease, the prognosis is typically poor.…”
Section: Introductionmentioning
confidence: 99%
“…However, tissue biopsies are invasive examinations that can only reflect the characteristics of tumors statically and locally at the biopsy location. Biopsies cannot be used for the dynamic monitoring of tumors during treatment and follow-up ( 6 ). Many disadvantages, including the risks associated with tissue biopsy (bleeding, infection, functional impairment, etc.…”
Section: Introductionmentioning
confidence: 99%